DEVELOPING TEACHERS’ DIDACTIC COMPETENCE IN ONLINE ENGLISH LANGUAGE EDUCATION - Kushimova Makhbuba Zhanibekovna (International Journal of Literature and Language Studies, 2026)
Abstract. The rapid integration of digital technologies into higher education has transformed English language teaching (ELT), shifting it from traditional face-to-face instruction to online and blended learning environments. This transformation has created new demands on teachers’ didactic competence, requiring not only linguistic and pedagogical knowledge but also the ability to effectively integrate digital tools into meaningful learning processes. This study investigates the development of teachers’ didactic competence in online English language education, focusing on challenges, essential competencies, and effective professional development strategies.